2019
DOI: 10.1177/0047287519894070
|View full text |Cite
|
Sign up to set email alerts
|

At Home or Abroad, Does Our Behavior Change? Examining How Everyday Behavior Influences Sustainable Travel Behavior and Tourist Clusters

Abstract: Considering the evolution of climate change and recognizing that the tourism industry is among the key contributors to this evolution, this study aims to clarify how researchers and practitioners can understand better what the triggers to the adoption of a sustainable behavior are while on holidays. Various studies have been conducted on the sustainable tourist, pointing to numerous characteristics but as of yet, not achieving an agreement as to what the profile of this type of tourist is. Through a study on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 42 publications
(89 reference statements)
9
94
1
Order By: Relevance
“…Furthermore, many studies that have examined age have found that older people are more ecologically conscious (Leonidou, Coudounaris, Kvasova, & Christodoulides, 2015), and they are more likely to be water conservers (Aprile & Fiorillo, 2017;Mallorquí et al, 2018). In contrast, other researchers indicated that younger people are more environmentally concerned (Holmes et al, 2019;Kiatkawsin & Han, 2017) and exhibited higher willingness to pay extra for towel reuse programs compared to older people (Chan, 2013;Dimara et al, 2017). In regards to education, many previous studies have found that highly educated individuals showed more sensitivity to ecological issues than those who are less educated (Fairweather et al, 2005;Holmes et al, 2019;Leonidou et al, 2015;Mallorquí et al, 2018).…”
Section: Impact Of Demographic Characteristics On Pro-environmentalmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, many studies that have examined age have found that older people are more ecologically conscious (Leonidou, Coudounaris, Kvasova, & Christodoulides, 2015), and they are more likely to be water conservers (Aprile & Fiorillo, 2017;Mallorquí et al, 2018). In contrast, other researchers indicated that younger people are more environmentally concerned (Holmes et al, 2019;Kiatkawsin & Han, 2017) and exhibited higher willingness to pay extra for towel reuse programs compared to older people (Chan, 2013;Dimara et al, 2017). In regards to education, many previous studies have found that highly educated individuals showed more sensitivity to ecological issues than those who are less educated (Fairweather et al, 2005;Holmes et al, 2019;Leonidou et al, 2015;Mallorquí et al, 2018).…”
Section: Impact Of Demographic Characteristics On Pro-environmentalmentioning
confidence: 96%
“…In contrast, other researchers indicated that younger people are more environmentally concerned (Holmes et al, 2019;Kiatkawsin & Han, 2017) and exhibited higher willingness to pay extra for towel reuse programs compared to older people (Chan, 2013;Dimara et al, 2017). In regards to education, many previous studies have found that highly educated individuals showed more sensitivity to ecological issues than those who are less educated (Fairweather et al, 2005;Holmes et al, 2019;Leonidou et al, 2015;Mallorquí et al, 2018). However, inconsistencies emerged from the research that investigated the impact of education on water conservation behavior.…”
Section: Impact Of Demographic Characteristics On Pro-environmentalmentioning
confidence: 96%
See 1 more Smart Citation
“…Tourism development is therefore more carbon intensive than previously believed, and it has a higher pollution propensity than other industries that could potentially be targeted for economic development (Bojanic and Warnick 2019). Successfully addressing this challenge requires not only a shift toward a more sustainable trajectory for both the tourists and the industry but also the engagement of scholars with wider debates in the social sciences regarding the economy-pollution nexus (Bramwell 2015;Bramwell et al 2017;Holmes, Dodds, and Frochot 2019;Knezevic Cvelbar, Gru¨n, and Dolnicar 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, tourism scholars, such as López-Sánchez and Pulido-Fernández [22], Jeong, Zielinski, Chang and Kim [23] and Choi, Kim, Sawitri and Lee [24], have focused on identifying segments of responsible tourists, with the aim of specifically targeting these individuals with sustainable tourism products. However, no consensus has been achieved on the profile of a sustainable consumer type [25]. Nevertheless, previous researchers show that the ratio of the tourists who would consume sustainable tourism products or behave responsibly towards the residents is considerably low [26,27].…”
Section: Literature Reviewmentioning
confidence: 99%